MISTRANSLATION OF LEGAL TERMINOLOGY RECONSIDERED - CHAN, Clara Ho-yan (Comparative Legilinguistics, 2017)
This study aims to explore different causes for the mistranslation of legal terminology in international agreements that are enforced through domestic legislation, and attempt to provide some solutions. It is said that legal training will help legal translators to render terminology correctly. This should be held true because many legal terms from different legal systems are ‘false friends’, in that even a well-trained lawyer may need to undertake extensive legal and linguistic research to render them in another language or legal system. This study, by use of a comparison of several translated legal terms from People’s Republic of China (PRC) and Taiwan, shows that besides the cause of ‘legal knowledge’, the disparities between international law and national law and different legal traditions can also lead to an improper transfer of legal terminology. Examples of these terms are “Copyright piracy” (Daoban 盗版 vs. qinhai zhuzuoquan 侵害著作权), “Good Faith” (Chengshi shouxin 诚实守信 vs. shanyi 善意), and “Inventive Step” (Famingxing de buzhou 发明性的步骤 vs. jinbuxing 进步性). In order to enhance translators’ legal knowledge, it is proposed that they be presented with some substantive laws together with simple illustrations of their structures. Translators should crosscheck their translations against a wide range of sources at work.